The relationship between spatial thinking ability and students' flood disaster location knowledge at MTsN 5 Klaten - Dwijayanti, Rani; Widyatmoko, Wahyu (Harmoni Sosial: Jurnal Pendidikan IPS, 2022)
Spatial thinking ability is a person's ability to represent an object around him that is associated with natural events. MTsN 5 Klaten is one of the schools that has experienced flooding. This study aims to (1) analyze the spatial thinking skills of MTsN 5 Klaten students, (2) analyze the location knowledge of students at MTsN 5 Klaten regarding flood disaster vulnerability, and (3) analyze the relationship between spatial thinking skills and location knowledge of students in MTsN 5 Klaten. This type of research is quantitative research. The total population of this study was all students of MTsN 5 Klaten, amounting to 348 students. The sample of this study amounted to 103 students who were taken by purposive sampling method because grade IX students had experienced flooding at MTsN 5 Klaten. Data collection techniques with interviews and observation questionnaires. Data analysis used descriptive statistics and correlation tests. The results showed that: 1) the spatial thinking ability of class IX students at MTsN 5 Klaten was in the medium category, with an average score of 40.78. 2) The ability of students' location knowledge to flood disaster vulnerability is included in the medium category with an average value of 75.01. 3) There is a relationship between the ability to think spatially and the location knowledge of students at MTsN 5 Klaten against the flood disaster. This can be seen from the value of t-count (7.22), which is greater than the t-table (1.66), so Ho is rejected, and H1 is accepted. The Rxy correlation test value is 0.583, included in the medium level with a coefficient of determination of 0.33 at a significance level of 5%.